Redefining the immune landscape of hepatitis A virus infection - Colasanti, Ombretta; Yu, Hosun; Lohmann, Volker; Shin, Eui-Cheol (Experimental & molecular medicine, 2025)
Despite the development of effective vaccines against hepatitis A virus (HAV) infection, outbreaks of acute hepatitis A still occur globally, such that HAV remains a major cause of acute viral hepatitis. Most patients with acute hepatitis A recover spontaneously; however, some adult cases result in acute liver failure due to immune-mediated liver damage. Previous studies suggested that HAV evades the innate immune response through strong counteractive mechanisms, and that HAV-specific CD8+ T cells contribute to liver damage in patients with acute hepatitis A. However, recent research findings have led to revisions of old hypotheses. Here we will describe the most current knowledge regarding the innate immune response to HAV and the HAV-mediated counteractions against innate immune responses. Additionally, we will discuss the roles of various types of T cells in viral clearance and liver injury in patients with acute hepatitis A.